Investigating the Relationship Between Serum Thyroid Hormone and Vitamin D Levels in Women with Melasma - Fahad, Majeed Ali (Al-Salam Journal for Medical Science, 2024)
Patches and macules of hyperpigmentation characterize melasma, a prevalent condition of skin pigmentation. Known risk factors for melasma include a genetic predisposition, sun exposure, and pregnancy. Melasma may have a connection to thyroid issues, according to previous research. Considering that vitamin D influences and promotes melanocytes' melanin formation, this study sought to examine the correlation between thyroid problems, blood vitamin D levels, and melasma in female patients seen at Al-Mahmoudiya Hospital. Both Wood's light investigation and clinical evaluation by seasoned dermatologists verified the melasma diagnosis. There were 80 participants in total, with 40 assigned to the melasma group and 40 to the control group. Their ages and sexes were matched. In all groups, blood samples were taken to assess levels of TSH, Anti-TPO, T3, T4, and vitamin D. Melasma patients' clinical pigmentation severity was assessed using the standard mMASI score. I used SPSS (IBM Statistical Package for the Social Sciences) version 21 to conduct the statistical analysis. Melasma patients were more likely to have thyroid problems (50%) and lower vitamin D serum levels (47.5%), compared to the control group (27.5%) and healthy individuals (40%). The levels of thyroid hormone (T3) and vitamin D were found to be considerably higher in the case group as compared to the control group (P<0.05). A relationship was found between Anti-TPO and mMASI Score (P< 0.05) when the relationship between age, thyroid hormones, vitamin D, and mMASI Score was investigated. Melasma and pigmentation intensity are linked to thyroid autoimmune diseases. The most prevalent clinical form of melasma is the centro facial variant as well.